2009
DOI: 10.1016/j.jacc.2009.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a Multiple Biomarkers Strategy Including Endothelial Dysfunction to Improve Risk Stratification for Cardiovascular Events in Patients at High Risk for Coronary Heart Disease

Abstract: The assessment of endothelial dysfunction by plasma levels of EMP can independently predict future cardiovascular events in patients at high risk for CHD. A multiple biomarkers strategy that includes endothelial dysfunction assessed by EMP can identify patients vulnerable to cardiovascular disease. (University Hospital Medical Information Network number: UMIN000000876).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(177 citation statements)
references
References 35 publications
5
166
0
3
Order By: Relevance
“…Preliminary data reported that baseline values of circulating CD62e + microparticles, measured before initiation of any specific therapy, predicted occurrence of adverse outcome (death and readmission for right heart failure) in a small cohort of patients with mixed aetiologies of PH [26]. Whereas these results were not observed for other EMP subsets (CD144 + and CD31 + EMPs) and should be confirmed in a larger population sample, they are in line with data reported in coronary artery disease [27], heart failure [28] and chronic end-stage renal failure [29], and thus confirm their potential role as a biomarker for outcome prediction in patients with cardiovascular diseases [30].…”
Section: Pulmonary Hypertension | N Amabile Et Alsupporting
confidence: 75%
“…Preliminary data reported that baseline values of circulating CD62e + microparticles, measured before initiation of any specific therapy, predicted occurrence of adverse outcome (death and readmission for right heart failure) in a small cohort of patients with mixed aetiologies of PH [26]. Whereas these results were not observed for other EMP subsets (CD144 + and CD31 + EMPs) and should be confirmed in a larger population sample, they are in line with data reported in coronary artery disease [27], heart failure [28] and chronic end-stage renal failure [29], and thus confirm their potential role as a biomarker for outcome prediction in patients with cardiovascular diseases [30].…”
Section: Pulmonary Hypertension | N Amabile Et Alsupporting
confidence: 75%
“…95 More recently, the hsCRP level improved the predictive value of the FRS in patients at high risk for coronary heart disease. 96 The independent prognostic value of the hsCRP level was also evident in a meta-analysis of 160,309 people without a history of vascular disease (ie, 1.31 million personyears at risk and 27,769 fatal or nonfatal disease outcomes) from 54 long-term prospective studies. 97 Ridker 98 reviewed evidence that hsCRP level correctly reclassifies a substantial proportion of patients at intermediate risk for CVD into clinically relevant higher-or lower-risk groups.…”
Section: Treatment Additional Cardiovascular Evaluation and Referralmentioning
confidence: 90%
“…In particular, acute reactions to infectious agents are associated with an increased risk of both arterial ischaemic events and VTE and are accompanied by both arterial and venous endothelial dysfunction (40,43,44); increased circulating levels of some biomarkers of endothelial dysfunction, like endothelial microparticles or P-selectin, are associated with both an enhanced risk of cardiovascular events and of VTE (45)(46)(47); recent data have shown in patients with VTE an increase of circulating fibronectin, an endothelium-released plasma factor previously shown to correlate with arterial endothelial dysfunction (48,49); several other clinical conditions characterised by an impaired arterial endothelial function, like airpollution, chronic HIV infection, a family history of myocardial infarction, the metabolic syndrome, rheumatoid arthritis and microalbuminuria, have been reported to be associated not only with an increased risk of arterial events but also of venous thrombosis (12,14,16,19,21,22,(50)(51)(52).…”
Section: (ǡTable 2)mentioning
confidence: 99%